Hypothesis: The opposing pulling forces exerted by spindle microtubules can cause sliding of chromatin layers and facilitate sister chromatid resolution - Daban, Joan-Ramon (Frontiers in Genetics, 2023)
Previous studies indicated that mitotic chromosome structure consists of many stacked layers formed by a mononucleosome sheet folded as a helicoid. This multilayer chromatin structure justifies the cylindrical shape of chromosomes and the transverse orientation of cytogenetic bands, and can explain chromosome duplication by the formation of a transient double helicoid that is split into two sister chromatids in mitosis. Here it is hypothesized that the bipolar pulling forces exerted by the mitotic spindle cause the sliding of the layers and facilitate sister chromatid resolution. This hypothesis is supported by three favorable conditions: (i) There is no topological entanglement of DNA between adjacent layers; (ii) The orientation (parallel to the stacked layers) of the bipolar kinetochore microtubules is adequate to produce layer sliding in opposite directions; (iii) The viscous resistance to the sliding caused by the weak interactions between nucleosomes in adjacent layers can be overcome by the microtubule pulling forces.